Integrating cross-discipline workshops for basic and clinical content treatment - Carlos Manuel Mora Hernández; Luis Alberto Mass Sosa; Ana Margarita López Rodríguez del Rey; Ada Sánchez Lozano; Anais Leiva Madrigal (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Educative spaces of social interaction result in excellent environments for explaining contents meaningfully, which generates true consciousness of its utility. The present article is aimed at offering assessments on the role of cross discipline integrating workshops for basic and clinical content treatment. The offered appraisals are based on three key elements: the importance of these workshops for constructing cross discipline knowledge, the value of socio-constructivist postulate for the subject who learns in these spaces and the authors' practical experience. It may be stated that from the conception assumed for their development, this type of workshop allows an adequate basic bio-medical and clinical content treatment in the Medicine career, since it is possible to achieve integrating specific objectives in learning new contents to be linked. In addition, they demand the use of teaching tasks for achieving these objectives and facilitate the use of didactic procedures for content treatment.